Pengaruh.Pengetahuan Perpajakan Dan.Penerapan E- Samsat Terhadap.Kepatuhan Wajib Pajak.Kendaraan Bermotor Dengan.Kesadaran Wajib.Pajak Sebagai Variabel Mediasi (Studi Kasus Pada Wajib Pajak kendaraan bermotor di SAMSAT Kabupaten Sukabumi) - Maspupah, Siti; Kusuma, Indra Cahya; Didi, Didi (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to determine how Tax Knowledge and E-Samsat Implementation affect Taxpayer Compliance, with a focus on the roleeof Taxpayer Awareness as a mediatinggfactor in motor vehiclee taxpayers registered at Samsat Sukabumi Regency 1 Cibadak. The]population-in this study]were`taxpayer}.registered.at}Samsat{with{a,totalioft400’taxpayers. TheiSlovintmethod was.used7for\sampling,.with1an,errot’rateuof.10%..Patrial’LeastoSquare;(PLS)]was.usedoin.this.study tokanalyzeithe.data. The1results.showed.that/there was]aniinfluence/between.knowledge and compliance while the/implementation/of’E-Samsat.had no]effect on\taxpayericompliance.iTaxpayer Awareness/was/able.to/mediateithe’influence[between’knowledge and’’the;implementation of E-Samsat onitaxpayer/compliance.